2021
DOI: 10.1111/hepr.13622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rifaximin, a poorly absorbed rifamycin antimicrobial agent, for hepatic encephalopathy in Japanese patients

Abstract: Aim Rifaximin is recommended as treatment for hepatic encephalopathy (HE) that targets intestinal bacterial flora. Although combined use with synthetic disaccharides is the standard of care worldwide, the therapeutic effects of rifaximin for overt encephalopathy (OHE) in Japanese patients have not been examined sufficiently. We examined the therapeutic effects of rifaximin for OHE in Japanese patients. Methods A total of 76 patients who developed OHE of West Haven grade II or higher at least once within the 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Rifaximin (Rifxima ® ; ASKA Pharmaceutical, Tokyo, Japan) was approved for the HE treatment in November 2016 in Japan. However, only data from clinical trials were available up to 12 weeks of administration [ 12 ], and data on the long-term efficacy and safety of rifaximin treatment have been limited in Japan [ 13 , 14 , 15 , 16 ]. Moreover, all data were obtained from a single-center retrospective study.…”
Section: Introductionmentioning
confidence: 99%
“…Rifaximin (Rifxima ® ; ASKA Pharmaceutical, Tokyo, Japan) was approved for the HE treatment in November 2016 in Japan. However, only data from clinical trials were available up to 12 weeks of administration [ 12 ], and data on the long-term efficacy and safety of rifaximin treatment have been limited in Japan [ 13 , 14 , 15 , 16 ]. Moreover, all data were obtained from a single-center retrospective study.…”
Section: Introductionmentioning
confidence: 99%
“…prevented the recurrence of HE and decreased the cumulative incidence of hospitalization associated with HE in Japanese patients. 2 They also reported that serum albumin level was an independent predictor of the efficacy of rifaximin, and a serum albumin level of 2.7 g/dl was considered the optimal cut-off for efficacy. Furthermore, they reported that the incidence of overt HE and the number of hospitalizations were significantly lower in patients with serum albumin levels ≥2.7 g/dl than in those with serum albumin levels <2.7 g/dl.…”
mentioning
confidence: 99%
“…6 In addition, only a few reports have evaluated the efficacy of rifaximin treatment in Japan. 2,[7][8][9] Recently, the long-term use of rifaximin has been reported to be safe and effective for HE in Japanese patients. 7 Hiramine et al also showed that 12 months of rifaximin treatment reduced ammonia levels and overt HE incidence and the number of hospitalizations.…”
mentioning
confidence: 99%
See 2 more Smart Citations